Perbandingan Pendapatan Usahatani Jagung Manis dan Padi di Subak Delod Sema Padanggalak Desa Kesiman Petilan Kecamatan Denpasar Timur - AGUSTYARI, NI KETUT; ANTARA, I MADE; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT Comparison of sweet corn and rice farm Income in Subak Delod Sema, Padanggalak Kesiman Petilan village, East Denpasar. Sweet corn as a farm commodities is a favorite food especially in town. Sweet corn cultivation has an opportunity to give high benefit if done by effective and efficient system. The election of research area is done by purposive because subak Delod Sema as a central of sweet corn in Denpasar. We take 35 sweet corn farmers and 15 rice farmers (opportunity cost)  from 177 sweet corn farmers as our respondent and we use Slovin Theory. Than 56 rice farmers (opportunity cost) with proportional random sampling method. The purposes of this research are for knowing farmer income, marketing process, and farmer problems. The result of this research show that real income rate which got by farmer from sweet corn farm operations are Rp 9,263,218 /month/ha bigger that's all million that is Rp 6,727,102/month/ha (57,01%) get more by rice as opportunity cost Rp 2,536,116/month /ha. This situation show that advantages in the same wide area for sweet corn farm operations get more value than rice cultivation. There are two ways for distribution their sweet corn product such as: first, start from farmer as producer to collector further to consumer. Second, start from farmer as producer to collector than collector to retail in market further to consumer. There are problem faced by sweet corn farmer such as: climate change, exchange price, rare access to investor, and decrease of price information. Based this research we suggest to farmer that sweet corn farm operations as daily profession and more active browsing information in create farm operations. Last for farmers and subak management know how to exploit their groups become to be marketing area. Key words: sweet corn farm operations and subak delod sema